Study of the biological efficiency of insecticides against locusts. - I.P. Umurzaqov; F.A. Gapparov; N.X. Tufliyev; A.F.Xaitmuratov; F.O. Nurjonov (Genius Journals, 2023)
It is important to fully understand the content of the price in the market of goods and services and to study a number of factors affecting its level. The variety of production and marketing conditions in various sectors and sectors of the economy and differences in the level of development of market relations create the need to differentiate types of prices. All types of prices operating in the economy constitute a price system. In a market economy, this article discusses in detail several types of prices.
Keywords: Price; dumping price; official price; national price